Preserving the Past: an Investigation into the Status and Conservation Efforts of Tangible Cultural Properties in Mariveles, Bataan, Philippines - Dela Rosa, John Albert (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of this study is to investigate the status and conservation efforts on the tangible cultural properties of Mariveles, Bataan, Philippines. Following the participatory cultural mapping approach, this research utilized the Cultural Mapping Toolkit and semi-structured interview questionnaire in gathering the data. As a result, this study identified tangible cultural properties which are categorized in movable and immovable. Moreso, the status and conservation efforts of the identified cultural properties were investigated. Based on the results, it is strongly recommended that the municipal administration of Mariveles, in collaboration with the BPSU and non-governmental organizations, develop a set of policies for the conservation of the identified tangible heritage. Additionally, the identified tangible cultural properties must be included in teaching in basic education.